Desenvolvimento e aplicação de revestimentos nanocerâmicos de zircônia em ligas níquel-titânio - Natalia Isabel de Azevedo Lopes (2018)
Corrosion and degradation of NiTi alloys used as biomaterials remain a concern due to toxicity, carcinogenicity, and allergenic effects associated with the release of nickel ions in the human body. Premature failures caused by corrosion and fatigue are also critical in biomedical applications of these alloys. In this work, the application of a nanostructured zirconia coating and its effects on the fracture and corrosion resistance of NiTi alloys were evaluated. Initially, the surface preparation of NiTi alloys was studied using electrolytic polishing. The results showed that electrolytic polishing reduces surface roughness, removes nickel-rich external layers and increases corrosion resistance of NiTi alloys. Subsequently, the optimal conditions for application of the zirconia coating were defined, using electrolytes containing zirconyl salts, with additions of methanol and a cationic polymer. The best results were obtained using a methanolic solution of ZrOCl2 with the addition of polyDADMAC. Then, a more complete characterization of the coating, obtained under these conditions, was performed, comparing the characteristics of the deposits formed on wires with and without surface preparation using electrolytic polishing. Analyzes of coating resistance and stability when submitted to corrosive environments and mechanical stresses, simulating physiological conditions, were also performed. The results showed that the coating obtained on the NiTi wire after electrolytic polishing is free of defects, more homogeneous and slightly thicker than that obtained without prior polishing. After immersion test in artificial physiological solution, for 12 months, the solubilized nickel was negligible, and the surface of the wires was covered by a layer of calcium phosphate, an indication of the bioactivity of the material. After bending and fatigue tests, cracks were observed in the coating, however, there was no significant delamination and the zirconia deposit maintained its protective properties. In general, the zirconia coating obtained in this study can be considered a good candidate for the improvement of surface properties of NiTi alloys for biomedical applications, including implants, stents, orthodontic wires, endodontic instruments, and others